Educational Connectivity and the Role of Generation Z in the Implementation of the Tourism Law - Taimenas, Elsa Dian; Lasibey, Ariance Ana; Malelak, Merlyn Luisa; Bentura, Fira Yuliance (Public Policy, 2025)
This study explores the critical connection between educational institutions and the regional tourism sector, focusing on Generation Z's role in implementing the Tourism Law in Kupang City. It highlights how the Tourism Department at Politeknik Negeri Kupang can prepare Generation Z for sustainable tourism development by aligning curricula with local industry needs and integrating technology and entrepreneurship. Based on Tourism Law No. 9 of 2010, educational institutions are pivotal in conducting research and supporting tourism policies. The study also emphasizes the importance of synergy among education, government, industry, and communities to achieve sustainable tourism growth. Its findings aim to provide a strategic guide for enhancing educational connectivity, effectively implementing tourism policies, and promoting community-based tourism to strengthen the local economy.